2010
DOI: 10.3233/jad-2010-100744
|View full text |Cite
|
Sign up to set email alerts
|

Dying with Dementia: What We Know after More than a Decade of Research

Abstract: Abstract. Death with dementia is increasingly common. Although prognostication is difficult, it is an incurable life-limiting illness for which palliative care for the patient is often appropriate. Dementia patients are otherwise at risk of overtreatment with burdensome and possibly non-beneficial interventions and undertreatment of symptoms. Although recent studies indicate encouraging trends of improved palliative care, little evidence supports effectiveness of specific treatments. As of January 2010, at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
177
1
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(192 citation statements)
references
References 177 publications
(275 reference statements)
2
177
1
11
Order By: Relevance
“…14 Such high-quality evidence is not yet available for palliative care in dementia, although dementia care at the end of life is increasingly being studied. 15 Disease trajectories differ for dementia and cancer patients. Cancer patients may experience a substantial decline in function in the last months or weeks of life, and diseased trajectories are relatively well-defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Such high-quality evidence is not yet available for palliative care in dementia, although dementia care at the end of life is increasingly being studied. 15 Disease trajectories differ for dementia and cancer patients. Cancer patients may experience a substantial decline in function in the last months or weeks of life, and diseased trajectories are relatively well-defined.…”
Section: Introductionmentioning
confidence: 99%
“…18 Survival is variable, and studies have reported means or medians of between about 3 and 10 years. 15,19 At an individual level, patients may survive to the last phase of dementia with severe physical and cognitive impairment but may also die earlier from dementia-related health problems such as pneumonia and intake problems or comorbid disease. [20][21][22] Therefore, prognostication in dementia is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Obstacles to accessing palliative care for those with dementia A plethora of literature exists advocating that people with dementia should have access to palliative care and hospice services (Mitchell et al, 2007;Birch and Draper 2008;Shega et al, 2008;Treloar et al, 2009;van der Steen, 2010;de Vries and Nowell, 2011). However, it is clear from the literature that people with end-stage dementia do not receive adequate or appropriate EoLC for a number of reasons; end-stage dementia is difficult to diagnose and dementia is often viewed as part of the natural ageing process (Phillips et al, 2011;Illiffe et al, 2013).…”
mentioning
confidence: 99%
“…We estimate the association between comorbidity burden and the following outcomes: emergency department admission, intensive care unit (ICU) admission, inpatient hospitalization, disenrollment from hospice, and hospital death. In addition, given the known challenges in caring for individuals with dementia, [17][18][19] we separately estimate the prevalence of comorbid dementia in the sample and the association between comorbid dementia and the previously listed outcomes.…”
mentioning
confidence: 99%